2021
DOI: 10.1021/acs.joc.1c01658
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed 2-(1-Methylhydrazinyl)pyridine-Assisted C–H Alkylation/Annulation: Mechanistic Insights and Rapid Access to Cyclopenta[c]isoquinolinone Derivatives

Abstract: We have developed cobalt-catalyzed, bidentate 2-(1methylhydrazinyl)pyridine (MHP)-directed C(sp 2 )−H alkylation/ annulation of benzoic hydrazides with various alkenes. Notably, diverse cyclopenta[c]isoquinolinones and dihydroisoquinolinones were obtained via this functional group-tolerant protocol. The reaction can be performed on a gram scale while maintaining an excellent yield, and the directing group can be removed efficiently under mild conditions. Furthermore, density-functional theory (DFT) calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Since the pioneering discovery of the 8-aminoquinoline-directed Co-catalyzed C–H alkenylation, 11 diverse cobalt-catalyzed C(sp 2 )–H annulations with alkenes, alkynes, allenes, and heterocycles were realized by different groups. 12–17 We initiated our investigation by exploring the cobalt-catalyzed coupling of C(sp 2 )–H bonds with ethylene as the model reaction, as was reported by Daugulis 12 a (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Since the pioneering discovery of the 8-aminoquinoline-directed Co-catalyzed C–H alkenylation, 11 diverse cobalt-catalyzed C(sp 2 )–H annulations with alkenes, alkynes, allenes, and heterocycles were realized by different groups. 12–17 We initiated our investigation by exploring the cobalt-catalyzed coupling of C(sp 2 )–H bonds with ethylene as the model reaction, as was reported by Daugulis 12 a (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Wu and coworkers [44] established a method for cyclopenta[ c ]isoquinolinones/dihydroisoquinolinones 39 synthesis via a Co(II)‐catalyzed C−H alkylation/annulation between benzoic hydrazides 37 and alkenes 38 (Scheme 15). The bidentate 2‐(1‐methylhydrazinyl)pyridine group acts as a directing group for Co‐catalyzed C−H activation.…”
Section: Metal‐catalyzed Synthesis Of Isoquinolinesmentioning
confidence: 99%
“…The synthetic value was further validated by the scale-up synthesis of one of the products. Various mechanistic studies were conducted and based on these studies and literature findings, they suggested that in the presence of air, Co Wu and coworkers [44] established a method for cyclopenta[c]isoquinolinones/dihydroisoquinolinones 39 synthesis via a Co(II)-catalyzed CÀ H alkylation/ Scheme 12. Synthesis and mechanism of tetrahydroisoquinolines 31 fused to tetrahydropyran ring using iron(III) chloride. )…”
Section: Cobalt Catalysismentioning
confidence: 99%
“…Very recently, Zhai, Wu and co-workers reported a cobalt-catalyzed C–H alkylation/annulation reaction of benzoic hydrazides 136 with alkenes 137 by using 2-(1-methylhydrazinyl)pyridine (MHP) as the directing group (Scheme 59). 84 A range of benzoic hydrazides with both electron-donating and -withdrawing substituents, alongside ethylene, cyclooctene, heteroaryl alkenes and styrene derivatives worked well, giving the desired cyclopenta[ c ]isoquinolinones 138 in moderate to excellent yields with good regioselectivities. However, unactivated terminal aliphatic alkenes give the corresponding products in low regioselectivities.…”
Section: Cobalt-catalyzed C–h Annulationmentioning
confidence: 99%